ANALISIS SISTEM AKUNTANSI BERBASIS TEKNOLOGI INFORMASI PADA PENGELOLAAN ANGGARAN DANA DESADI DESA SARI MAKMUR KABUPATEN MUKOMUKO - dewi aprida; iwin Arnova (Jurnal Ilmu Akuntansi, 2025)
The purpose of this research to analyze accounting system based on information technology to village fund budget management in Sari Makmur village Mukomuko regency. This research method uses descriptive. The sample in this study consisted of 30 respondents, selected using non-probability sampling techniques and data collection was obtained by distributing questionnaires. The research result show that analyze accounting system based on information technology has positive influence on the village apparatus performance and the village fund management. Positive means that by implementing accounting system based  on information technology in the village office, it can improve the quality of village apparatus performance and the efficiency of village fund management.